2011
DOI: 10.1042/bst0390984
|View full text |Cite
|
Sign up to set email alerts
|

Plasma PLTP (phospholipid-transfer protein): an emerging role in ‘reverse lipopolysaccharide transport’ and innate immunity

Abstract: Plasma PLTP (phospholipid-transfer protein) is a member of the lipid transfer/LBP [LPS (lipopolysaccharide)-binding protein] family, which constitutes a superfamily of genes together with the short and long PLUNC (palate, lung and nasal epithelium clone) proteins. Although PLTP was studied initially for its involvement in the metabolism of HDL (high-density lipoproteins) and reverse cholesterol transport (i.e. the metabolic pathway through which cholesterol excess can be transported from peripheral tissues bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 56 publications
(46 reference statements)
5
67
0
Order By: Relevance
“…Finally, calculation of the LAL (activity) to HPLC/MS/MS (mass) LPS ratio is proposed as a relevant method to assess in vivo the effi cacy of the initial step of LPS neutralization [known as the endotoxin-lipoprotein hypothesis ( 29 )]. This step is followed by lipoprotein-mediated transport to the liver and ultimate detoxifi cation in the bile ( 30,31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, calculation of the LAL (activity) to HPLC/MS/MS (mass) LPS ratio is proposed as a relevant method to assess in vivo the effi cacy of the initial step of LPS neutralization [known as the endotoxin-lipoprotein hypothesis ( 29 )]. This step is followed by lipoprotein-mediated transport to the liver and ultimate detoxifi cation in the bile ( 30,31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, pathogen lipids can be sequestered and cleared from the circulation, potentially diminishing their inflammatory effect (4-6) (Figure 1). In this review we address the hypothesis that sequestration and clearance of pathogen lipids may be beneficial and feasible in treating septic patients (4).…”
Section: Introductionmentioning
confidence: 99%
“…40 It was recently shown that there is an alternative route of LPS elimination, by binding to HDL and elimination in the liver. 41 According to Hailman et al, PLTP may be a key mediator in binding LPS to HDL. 42 Incubation of LPS with HDL in the presence of PLTP leads to the binding of the particles.…”
Section: Animal Modelsmentioning
confidence: 99%
“…According to Gautier and Lagrost, PLTP may play a role in the reverse transport of LPS, as in the transport of cholesterol. 41 Mice with naturally high levels of PLTP were observed to have lower concentration of LPS and they develop less severe inflammation. Moreover, the reverse LPS transport via HDL and PLTP may increase the rate of elimination of LPS by biliary excretion.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation